Deep learning-based instructional innovation in pancasila education for meaningful student learning outcomes - Meljulia Sartika; Al Rafni; Hasrul Piliang; Junaidi Indrawadi (Global Econedu, 2026)
This study aimed to examine the implementation of deep learning-based instructional innovation in Pancasila Education at State Junior High School 1 of Solok City. A descriptive qualitative approach was employed involving 13 purposively selected informants consisting of one principal, four Pancasila Education teachers, and eight students. Data were collected through observations, semi-structured interviews, and document analysis, then analyzed using the Miles and Huberman interactive model with triangulation to ensure trustworthiness. Deep learning was implemented through contextual learning, project-based activities, authentic assessment, reflective learning, and digital media integration. These practices enhanced student engagement, critical thinking, collaboration, and the internalization of Pancasila values despite challenges related to teacher readiness, limited instructional time, technology, and curriculum demands. Deep learning effectively strengthens instructional quality and character development in Pancasila Education, although sustained implementation requires continuous professional development and institutional support